Foreign Language Acquisition at Elementary Level Education in Samarinda - Muklis, Mohamad; Noor, Widya Noviana; Yuandari, Sherly (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
The main objective of this study is to investigate the process of foreign language acquisition of certain kid in Samarinda, as the capital city of East Kalimantan, Indonesia. Two months case study have already conducted to capture all phenomenon happened especially towards important factors from several experts which are potentially influenced the process of L2 acquisition i.e. general factors e.g. aptitude, age, intelligence, cognitive, attitude, motivation, and personality (Ellis, 2008), linguistics input including formal and informal environments (Krashen, 1981), and three second language believes i.e. behaviorist, innatist, and interactionist (Lightbown & Spada, 2006). Direct observation to the subject condition and environment was done as well as semi-structured interview to obtain deeper information from the caregiver who has direct interaction with the subject every day. As the result, the findings indicate that a proper stimulus can motivate the subject to learn and acquire the L2 even though stable proportion from both formal and informal environments as linguistics input should be noticed in order for the subject to have better achievement on her L2 acquisition. Other factors influenced the L2 acquisition of the subject is also explained following by its implications and suggestions regarding with this research focus.